The Effect of the Jigsaw Cooperative Learning Model on Students’ Learning Outcomes in Ecology and Biodiversity - Syarah, Putri Mei; Dimenta, Rivo Hasper; Sari, Novi Fitriandika (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the effect of the Jigsaw cooperative learning model on students’ learning outcomes in Ecology and Biodiversity among seventh-grade students at MTsN 1 Labuhanbatu. A quantitative approach was employed using a quasi-experimental design with a pretest-posttest control group. The sample consisted of 64 students from two classes: Class VII-I as the experimental group and Class VII-F as the control group, selected through cluster random sampling. Data were collected using a validated and reliable multiple-choice achievement test. Data analysis involved prerequisite testing and hypothesis testing using SPSS version 25. The results showed that the mean posttest score of the experimental group was 80.62, which was higher than that of the control group, with a mean score of 59.87. The hypothesis test indicated that the Jigsaw cooperative learning model significantly improved students’ learning outcomes in Ecology and Biodiversity compared with conventional teaching methods, as indicated by Sig. (2-tailed) = 0.000 (p < 0.05). These findings suggest that students’ engagement in home groups, expert groups, and peer-teaching activities contributed to improved conceptual understanding of Ecology and Biodiversity. This study implies that the Jigsaw cooperative learning model can serve as an alternative instructional strategy to enhance students’ learning outcomes and active participation in science learning.